Vaccine fake news: an analysis under the World Health Organization’s 3Cs model - Gomes Frugoli, Alice; de Souza Prado, Raquel; Moreira Ribeiro da Silva, Tercia; Penido Matozinhos, Fernanda; Andrea Trapé, Carla; Aparecida Ferreira Lachtim, Sheila (Revista da Escola de Enfermagem da USP, 2021)
Objective To analyze fake news about immunobiologicals using as reference vaccine hesitancy in the World Health Organization’s 3Cs model (confidence, complacency and convenience). Method This is an exploratory qualitative research that used content analysis to analyze fake news on three national news-checking sites. Results Twenty fake news related to immunobiologicals were analyzed, with 55% published in 2018 and 63% related to yellow fever vaccine. From analysis of results, two empirical categories have emerged: Immunobiologicals have a potential risk of death/sequel; Immunobiologicals are ineffective. Conclusion Fake news have the potential to produce vaccine hesitancy based on the 3Cs model. Therefore, it is necessary to rethink communicative health practices that do not underestimate the asymmetries and inequities that characterize the unequal Brazilian society. Considering that nursing is the largest workforce in immunization rooms, there is a need for professionals’ engagement as an active vehicle of truthful information in immunobiologicals for the population.